The feasibility of doing multi-level marketing in Moccis Trading Sdn. Bhd. / Laili Maryana Mohd. Saleh - Mohd. Saleh, Laili Maryana (1998)
Multi Level Marketing or better known as MLM is a form of marketing concept which involves the appointment of individuals to market products or services through direct selling to other individuals in return for commission earned for every completed sale. It does not require a huge capital nor outlet or even a business centre for an individual-to be involved in this kind of business. Hard work and good communication skills are all it takes for an individual to have a large customer base.